PENGARUH MODAL KERJA, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN PT.MANDIRI MART - Abdul Wachid; Kardi; Fitri Miswati (JURNAL AS-SAID, 2022)
This study was conducted to test the effect of the variables of Working Capital, Accounts Receivable Turnover, Inventory Turnover on Profitability at PT. Mandiri Mart Company in Batan 2020. The population in this study was 56 trading companies in Batam. The sampling technique or sample is 30 companies. Data obtained from the company's financial statements and interviews with the company's management. The results of this study indicate that simultaneously the variables of working capital, accounts receivable turnover and inventory turnover have a significant effect on profitability. Likewise, the results of research conducted partially indicate that the variables of working capital, accounts receivable turnover and inventory turnover have a significant effect on profitability.Keywords: Working Capital, Accounts Receivable and Inventory Turn over, company profitability.